THE RECYCLING POTENTIAL OF SOLID WASTE IN JATINEGARA SUB-DISTRICT, EAST JAKARTA - Alfa Miranti Kuntaryo; Pramiati Purwaningrum; Tazkiaturrizki; Astari Minarti; Fitrio Ashardiono (Universitas Trisakti, 2023)
Aim: This study aims to analyze the recycling potential of solid waste in Jatinegara sub-district as a basis for optimizing solid waste management with the 3R principle. Methodology and Results: The sampling method to calculate the waste generation rate and composition was based on SNI 19-3964-1994. The sampling results showed that the average waste generation of Jatinegara sub-district was 0.22 kg/person/day or 2.02 liters/person/day. With a population of 328,345 in 2020, the waste generation is 663,055 L/day or 663.05 m3/day. The waste composition comprises 55.02% organic waste and 44.98% non-organic waste. The composition of organic waste that has the potential to be reprocessed is 38.52%. The potential for recycling non-organic waste is determined by identifying the types of waste that waste banks can accept. The composition of non-organic waste that can be recycled is 26.11%. Non-organic waste that has the potential to be sold to waste banks is 96.26% of total plastic waste, 100% of paper waste, 100% of metal waste, and 100% of glass/glass waste. Conclusion, significance and impact study: The total waste that can be recycled in Jatinegara sub-district is 64.62%, and the residue generated is 35.38%. Recycling can reduce waste to 372.76 m3/day.